STYLISTIC OF PAMBIWARA PANGGIH TEMANTEN SURAKARTA - Nugraheni Setyaningrum; Wakit Abdullah; Dwi Purnanto (Proceeding of International Conference on Art, Language, and Culture, 2017)
This study aims to describe the uniqueness and uniqueness of the use of language style (sounds of language, morphology aspect, diction, and imaging) in pambiwara panggih temanten style Surakarta. In this research, the researcher uses descriptive qualitative by using stylistic approach. Sources of data in this study is a source of written data in the form of a text pambiwara Surakarta.  The data source is in the form of oral data source delivered by pambiwara from informants. The data in this research is orthographic transcription of pambiwara panggih temanten in Javanese Surakarta. The basic technique used by using the listening technique, it is obtained data by listening the use of language. In this research, the researcheruses stylistic analysis of sentences in the Javanes language, and also using listening techniques and record techniques. The results of this study shows that the temanten style Surakarta style has the beauty of the language text: (1) Sound beauty aspect (asonansi (purwakanthiswara), alliteration (purwakanthi sastra), repetition (purwakanthilumaksita), (2) Diction beauty aspect (usage of various tembung kawi, dasanama), (3) morphological beauty aspect (prefix, suffix, confix, dwipurwa / iteration), and (4) imagery to describe the bride.